Iqbāl āʼīnah ḵẖāne meṉ : maqālāt va taqārīr, Iqbāl Samīnār munʻaqidah Bhopāl - Aḥmad, Āfāq (Madhyah Pradesh Urdū Akaiḍmī, 1979)
On the life and works of the Urdu poet Sir Muhammad Iqbal, 1877-1938; papers read at the Iqbal Seminar held in Bhopal, 1978.